Politically Sensitive Encounters: Ethnography, Access, and the Benefits of “Hanging Out” - Browne, Brendan Ciarán; McBride, Ruari-Santiago (Qualitative Sociology Review, 2015)
Negotiating politically sensitive research environments requires both a careful consideration of the methods involved and a great deal of personal resolve. In drawing upon two distinct yet comparable fieldwork experiences, this paper champions the benefits of ethnographic methods in seeking to gain positionality and research legitimacy among those identified as future research participants. The authors explore and discuss their use of the ethnographic concept of “hanging out” in politically sensitive environments when seeking to negotiate access to potentially hard to reach participants living in challenging research environments. Through an illustrative examination of their experiences in researching commemorative rituals in Palestine and mental health in a Northern Irish prison, both authors reflect upon their use of “hanging out” when seeking to break down barriers and gain acceptance among their target research participants. Their involvement in a range of activities, not directly related to the overall aims of the research project, highlights a need for qualitative researchers to adopt a flexible research design, one that embraces serendipitous or chance encounters, when seeking to gain access to hard to reach research participants or when issues of researcher legitimacy are particularly pronounced, such as is the case in politically sensitive research environments.